Sarcoma ecotypes determine immunotherapy benefit - Wagner, Johanna; Fröhling, Stefan (Nature cancer, 2024)
Sarcomas are heterogeneous connective tissue tumors that occur at various anatomic sites and are generally difficult to treat. Cell states in sarcoma ecosystems are now shown to be conserved across multiple subtypes and associated with response to immunotherapy and patient outcome.
Gesehen am 16.10.2024